2021
DOI: 10.3390/polym13193280
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the α/δ Crystal Transition of Poly(l-lactic Acid) with Different Molecular Weights

Abstract: Poly(l-lactic acid) (PLLA) crystal possesses a complex polymorphism, and the formation mechanism of various crystal forms has been a hot research topic in the field of polymer condensate matter. In this research, five kinds of PLLA with different molecular weights were prepared by ring-opening polymerization with strict dehydration operations and multistep purification treatments. Then, thin film isothermal crystallization experiments were carried out to obtain crystallized samples. Previous research has prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
3
6
1
Order By: Relevance
“…The occurrence of elliptical pores (average values of a = 0.23 ± 0.05 µm and b = 0.09 ± 0.02 µm) along the fiber axis were measured to have a periodic distance of around 2 ± 0.2 µm. The lamellar periodic distance mentioned in the literature for crystalline PLA is in the range of nanometers [43], unlike the values reported in this study. Since this degradation study was limited to only 25 days, a further decrease in the periodicity of the pores could be anticipated as more pores are likely to form over prolonged degradation times.…”
Section: Discussioncontrasting
confidence: 99%
“…The occurrence of elliptical pores (average values of a = 0.23 ± 0.05 µm and b = 0.09 ± 0.02 µm) along the fiber axis were measured to have a periodic distance of around 2 ± 0.2 µm. The lamellar periodic distance mentioned in the literature for crystalline PLA is in the range of nanometers [43], unlike the values reported in this study. Since this degradation study was limited to only 25 days, a further decrease in the periodicity of the pores could be anticipated as more pores are likely to form over prolonged degradation times.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, T 225 with low crystallinity and T 80 with an α′ crystal exhibited diffuse and broad scattering, which is an indication of the low electronic density difference between the crystalline and amorphous phases. The diffuse SAXS pattern of the α′ crystal, even with the periodic lamellae structure, has been observed in other studies as well. For example, Díez-Rodríguez et al found that in samples annealed at 75 °C, which developed a primary α′ crystal, no long-spacing peak was detected. This diffuse SAXS pattern without the long-spacing maximum in the α′ crystal can be ascribed to the conformational disorder, ,, where partial chains in the unit cell of the α′ crystal may adopt the helix conformation other than 10 3 as the most do and distribute randomly in the unit cell. , Such a disorder could decrease the electronic density difference between the crystalline and amorphous phases, showing a diffuse SAXS pattern .…”
Section: Resultssupporting
confidence: 52%
“…Upon heating, PLA initially transitions from the glassy state to the rubbery state, where molecular mobility increases [41,42]. As the temperature further increases, the polymer chains rearrange into the α ′ -crystalline form, leading to a slight displacement of the curve [29,43,44]. The α ′ -crystalline form of PLA is less ordered and exhibits lower crystallinity levels than the α-crystalline form.…”
Section: Dsc Analysismentioning
confidence: 99%